African Women of the Screen: an Agenda for Research - Ellerson, Beti (Africana Studia, 2020)
African women in cinema studies, a nascent field of research which has taken shape during the past ten years, is located at the intersection of African women research methodology, women’s studies, screen studies, African studies, transnational cinema and feminist film theory. Its epistemological approach frames the voices and live experiences of African women image-makers at the center of exploration; it proposes an alternative discourse. The paper offers an agenda for future research and study, outlining a selection of themes relevant to African women in cinema studies: the role of the filmmaker in the production of knowledge; African women’s cinematic gaze as alternative discourse: a theory-practice-activist approach; identity and screen practices; training, formation and cinematic identity. Keywords: feminist film theory, African studies, women studies, transnational cinema.